2008
DOI: 10.1002/chem.200801135
|View full text |Cite
|
Sign up to set email alerts
|

2‐Phenanthrenyl–DNA: Synthesis, Pairing, and Fluorescence Properties

Abstract: Three 2′‐phenanthrenyl‐C‐deoxyribonucleosides with donor (phenNH2), acceptor (phenNO2), or no (phenH) substitution on the phenanthrenyl core were synthesized and incorporated into oligodeoxyribonucleotides. Duplexes containing either one or three consecutive phenR residues, which were located opposite each other, were formed. Within these residues, the phenR residues are expected to recognize each other through interstrand stacking interactions, in much the same way as described previously for biphenyl DNA. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 62 publications
1
34
0
1
Order By: Relevance
“…It was used to explore environmental and dynamics features of DNA oligonucleotides 428,444452. A phenanthrenyl nucleoside, recently reported by Leumann, was used to explore electron transfer in DNA 453,454…”
Section: Fluorescent Nucleoside Analogsmentioning
confidence: 99%
“…It was used to explore environmental and dynamics features of DNA oligonucleotides 428,444452. A phenanthrenyl nucleoside, recently reported by Leumann, was used to explore electron transfer in DNA 453,454…”
Section: Fluorescent Nucleoside Analogsmentioning
confidence: 99%
“…This effect was observed in earlier studies with non-hydrogen bonding base surrogates and was found to be an enthalpy driven process induced by the increased hydrophobic interactions of such base surrogates. [11,15] An expected decrease in stability was observed for duplexes containing electron donating groups and vice versa a stabilization of duplexes containing electron withdrawing groups. Circular dichroism (CD) spectroscopy revealed that the secondary structure of natural DNA is not disturbed by the phenanthrenyl or pyrenyl modifications.…”
Section: Nh2mentioning
confidence: 96%
“…The synthesis of the NH2 phen and phen phosphoramidites applicable for automated DNA synthesis was performed according to published procedures. [11] The introduction of a cyano group required a palladium catalyzed substitution of the In order to study the EET properties through phenanthrenyl base surrogates a α-C-nucleosidic dimethylamino-pyrene (C-AP) was synthesized that could intercalate well against an abasic site, which enables an efficient photo induced electron injection due to the close proximity to the phenanthrenyl stack. [12] The synthesis involved a nucleosidation of the chloro Hofer sugar and a Gilman cuprate [13] of the 6-bromo-N,N-dimethylpyren-1-amine, which was received from bromination, nitrification, reduction and dimethylation of the amine function of the pyrene (see Scheme S1 and Scheme S2 in ESI).…”
mentioning
confidence: 99%
“…The sample temperature was increased by 0.5°C min -1 . The thermodynamic parameters of the duplexes on duplex formation were determined by calculations based on the slope of a 1/T m vs. ln(C T /4) plot, where C T (2,4,6,10,16,26,44,70,120, and 200 µ) is the total concentration of single strands.…”
Section: Thermal Denaturation Studymentioning
confidence: 99%